Returning of Irregular Migrants and Legal Certainty in Specific Central European States: A Comparative Perspective - Tchórzewski, Mateusz (Migration and Central Europe: Challenges and Legal Responses, 2024)
The study is dedicated to the question of returning irregular migrants from the point of view of issues related to legal certainty. The topic is approached from a comparative perspective considering chosen Central European states: Hungary, Poland, Slovakia, the Czech Republic, Croatia, Slovenia, and Romania. These countries are characterised by distinct approaches to addressing irregular migration. The study juxtaposes and analyses these approaches. A concise analysis of the notion of legal certainty is conducted. It emphasizes the importance of ensuring predictability from the point of view of affected migrants. The study then discusses the relevant pieces of legislation that regulate the situation of migrants in these particular states. Court decisions, including selected judgements of national constitutional and administrative courts as well as specific judgements of the Court of Justice of the European Union and the European Court of Human Rights, are considered. Certain tensions, related to the relationship between national law and the law of the European Union, can be observed in some instances. These tensions may be seen as detrimental from the point of view of realising the principle of legal certainty and should be addressed by either modifying the EU’s policies regarding migration or by granting Member States more discretion in terms of managing the aforementioned issue. This need is a result of divergent circumstances and related attitudes which exist in different states. These circumstances include, but are not limited to, the coercive engineered migration which should be viewed in the broader context of the security situation in Northern and Central Europe.Keywords: returning irregular migrants, legal certainty, migration crises.